2007
DOI: 10.1371/journal.pmed.0040108
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant DNA Methylation of OLIG1, a Novel Prognostic Factor in Non-Small Cell Lung Cancer

Abstract: BackgroundLung cancer is the leading cause of cancer-related death worldwide. Currently, tumor, node, metastasis (TNM) staging provides the most accurate prognostic parameter for patients with non-small cell lung cancer (NSCLC). However, the overall survival of patients with resectable tumors varies significantly, indicating the need for additional prognostic factors to better predict the outcome of the disease, particularly within a given TNM subset.Methods and FindingsIn this study, we investigated whether a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
30
0
1

Year Published

2008
2008
2012
2012

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(31 citation statements)
references
References 50 publications
0
30
0
1
Order By: Relevance
“…Pathological deregulation of such scaffolds is likely to have deleterious effects. Of note, BAHD1 expression is down-regulated in invasive lung cancer cells (8), and a recent study indicated reduced levels of BAHD1 transcript in RNA in blood samples from patients with double tumors compared with patients with single tumors (http:// www.nextbio.com/b/home/home.nb?q ϭ BAHD1). Our findings support the hypothesis that BAHD1 acts as a tumor suppressor through the silencing of cancer-related genes, such as IGF2, in adult tissues.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pathological deregulation of such scaffolds is likely to have deleterious effects. Of note, BAHD1 expression is down-regulated in invasive lung cancer cells (8), and a recent study indicated reduced levels of BAHD1 transcript in RNA in blood samples from patients with double tumors compared with patients with single tumors (http:// www.nextbio.com/b/home/home.nb?q ϭ BAHD1). Our findings support the hypothesis that BAHD1 acts as a tumor suppressor through the silencing of cancer-related genes, such as IGF2, in adult tissues.…”
Section: Discussionmentioning
confidence: 99%
“…During a screen for human proteins that interact with microbial factors and that might play a role in bacterial pathogenicity, we identified a putative chromatin-associated protein, bromo adjacent homology domaincontaining protein 1 (BAHD1), which remains uncharacterized. One study correlated repression of the BAHD1 gene to poor prognosis in lung cancer (8), raising the possibility that BAHD1 might act as a tumor suppressor. This connection between BAHD1 and pathological processes prompted us to characterize the function of this protein.…”
mentioning
confidence: 99%
“…Nonquantitative MSP may be useful for these applications, especially when quantitative levels would have little value due to variable sample composition, such as may occur with very small biopsies or cytologic specimens. Finally, genome-wide comparative analysis of CpG methylation patterns in normal tissues and tumors may require microarray approaches, 53 although validation requirements for such techniques are inherently complex and not yet well-established.…”
Section: Selection Of Methods For Testing Methylation Of Specific Cpgmentioning
confidence: 99%
“…13 Overexpression of DNA methyltranferases DNMT1, DNMT3A and DNMT3B has been described in NSCLC especially among smoker patients, and correlates with hypermethylation of tumor suppressor gene such as p16 INK4a , FHIT and RARβ. 17,18 Furthermore, polymorphisms that influence expression of the DNMT3B gene have been connected with risk of lung cancer.…”
mentioning
confidence: 99%
“…Consistently, genome wide analyses have pointed to the fact that the extend of promoter DNA hypermethylation is probably under-appreciated. [13][14][15][16] By using a high-throughput global expression profiling approach, Shames et al recently identified 132 genes that are methylated with high penetrance in lung cancer cells. 16 More strikingly, the analysis performed by Brena et al supports the notion that 4.8% of all CpG island promoters might be aberrantly methylated, suggesting that the expression of about 1,400 genes might be disturbed These modifications can either favor (e.g., acetylation, methylation) or inhibit (e.g., methylation) the access to the chromatin and are involved in all DNA-based processes described so far.…”
mentioning
confidence: 99%